Telehealth in community mental health centers during the COVID-19 pandemic in Peru: A qualitative study with key stakeholders - Rubí Paredes-Angeles; Victoria Cavero; Ana L. Vilela-Estrada; Noelia Cusihuaman-Lope; David Villarreal-Zegarra; Francisco Diez-Canseco (Elsevier, 2024)
Aim: To describe the perceptions and experiences of key stakeholders to understand the use of telehealth in community mental health centers (CMHCs) during the COVID-19 pandemic in Lima and Callao, Peru. Methods: A qualitative study was carried out in four CMHCs in Lima and Callao, Peru. Forty-nine individual semi-structured interviews were conducted between September 2021 and March 2022, considering CMHCs' users and their relatives, health and administrative workers, directors, as well as local and national policymakers. Data was analyzed using thematic analysis. Results: Regarding the transition from in-person care to telehealth, CMHCs' directors and workers identified some of the regulations issued by the Government during the pandemic, such as the continuity of care through telehealth, especially for pregnant women and for people with comorbidities related to COVID-19. Regarding benefits, workers and users indicated that it allowed better communication, such as constant follow-ups. Directors and workers recognized that Google Drive facilitated access to user information, since they did not have an electronic medical record. Additionally, workers said they used social media to share educational information on mental health, and explained that some new users began their treatment this way. Regarding difficulties, participants reported a lack of devices and poor internet connection in CMHCs. Users mentioned that scheduling an appointment was difficult because the phone lines were usually saturated, and they could not find available appointments. Conclusion: Although the pandemic forced an immediate and disruptive change towards telehealth, CMHCs were able to adapt most of their services. This study reports the adaptations made by CMHCs to move from in-person to remote care, identifying the benefits and challenges faced, information that can be used for the nationwide implementation of telehealth in CMHCs. We recommend ensuring technological equipment and internet connection and adapt the telehealth system to make it responsive to the routine practices of CMHCs.